Isometric force, tethered force and power ratios as tools for the evaluation of technical ability in freestyle swimming - Rouard, A. H.; Aujouannet, Y. A.; Hintzy, F.; Bonifazi, M. (Biomechanics and Medicine in Swimming X, 2006)
The aim of this study is to determine the relationships between isometric force, tethered force and force developed during maximal power test. Eighth international swimmers realised maximal isometric forces for 3 arm-trunk angles (Fiso30°, Fiso90°, Fiso120°). Then, a 5s full tethered swim allowed the measure of the maximal propulsive force in water (Fpmax). Finally, a 25m maximal power test was realised in a 1/2 tethered condition. Isometric forces were not significantly different for the 3 angles. Large individual variations were observed for the ratio Fpmax/Fiso30° as for the ratio Fp/Fpmax reflecting different technical abilities and/or different compromise force-velocity. Fiso30° was significantly correlated to Fpmax and to Fp. The technical ability appeared determinant to transform strength capacity in specific swimming force. These results could be useful to determine the swimmer's insufficiencies, i.e., low isometric force and/or bad technical ability.